ANTIULCEROGENIC BENEFITS OF HERBAL INGREDIENTS IN ETHANOL-INDUCED ANIMAL MODELS - Bi, Weiping; Man, Huibin; Hu, Lizhi; Man, Mao-Qiang (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
pathogenesis of gastric ulcer. Although therapeutic approaches are widely available, preventive regimens are limited. Numerous studies have demonstrated that herbal medicines display preventive benefit in the development of ethanol-induced gastric ulcers in both rat and mouse models. The preventive efficacy of herbal medicines on the development of ethanol-induced gastric ulcers is comparable or superior to histamine receptor 2 antagonists. But herbal medicines have fewer side effects. Materials and Methods: Keywords including gastric ulcer, herbal medicines, prevention and natural ingredients were used to search on http://www.ncbi.nlm.nih.gov/pubmed. The search was performed on January 12, 2014. Only articles published in English were used in this review. Result and Conclusion: According to the mechanisms of their action and pathogenesis of gastric ulcer, combination of certain herbal medicines could be a valuable alternative to prevent the development of gastric ulcer, particularly for the subjects who are at a higher risk of developing gastric ulcer.